Do Institutional Investors Improve The Corporate Goverance? - A Study of Public Listed Companies in Malaysia - Zhu, Xia (2008)
This study is based on the top 100 ranking listed companies on the corporate governance in Main Board of Exchange in Malaysia by the end of December in 2007. Among these 100 companies, according to the percentage shareholdings owned by the institutional investors in each company of 2006, I will investigate that if the more percentage shareholding by the institutional investors, the higher ranking of the corporate governance of the company. In other words, I am trying to find out if the institutional investors are able to improve the corporate governance in Malaysia in 1 year time. With the help of Kruskal-Wallis test (one-way ANOVA), I find that there are very big differences of the percentage shareholdings of the institutional investors among different ownership structure companies (Government-Linked Company, Family-Controlled Company, Multinational Company and Others), the specialty of this study from others is that I divide the 100 companies into 4 groups, and testify the effect of institutional investors (domestic plus foreign) on corporate governance separately via Spearman’s order correlation test. Moreover, the extent of the impact of institutional investors on the corporate governance is also attempted to be evaluated. Besides, the impact of institutional investors on corporate governance also depends on the nature of them. Therefore, I classified the domestic and foreign institutional 7 investors into 2 groups: one is pressure insensitive investors (domestic and foreign long-term and stated-owned institutional investors) and another is pressure sensitive investors (domestic and foreign short-term and private institutional investors). Finally, the foreign institutional investors are extracted from the total shareholdings, and its impact on improvement of corporate governance will also be investigated in more detail. In addition, beyond the univariate and bivariate analysis to test of differences and association between variables, the multiple regression as the extension of the correlation will be used to represent the best prediction of corporate governance score from 2 independent variables (ownership structure and shareholdings of institutional investors). The findings of this study are: The shareholdings owned by institutional investors in 4 ownership groups are quite different from each other. Among of these, shareholding of institutional investors in GLCs’ is the highest one, followed by MNCs and FCCs. As to the impact of institutional investors (domestic plus foreign) on the good corporate governance, the pressure sensitive institutional investors can improve the corporate governance in FCCs and GLCs for one year time, but not in MNCs. For the foreign institutional investors, the foreign institutional investors themselves can make the corporate governance improved in one year time in GLCs. As to the FCCs and MNCs, the positive effects are not significant on corporate governance.